Strenthening of alumunium with addition of nano-silicon carbide by using powder metallurgy method / Rizal Mohamed Noor, Khairul Fauzi Karim and Kamrol Amri Mohamed. - Mohamed Noor, Rizal; Karim, Khairul Fauzi; Mohamed, Kamrol Amri (2006)
This study focuses on nano silicon carbide particulate-reinforced metal-matrix composites processing route using two different powder metallurgy techniques; cold press-sintered and hot press-vacuum. Two kinds of SiC particulates (SiCp), whose diameters 60 pm and 50-200 nm were separately incorporated into Al-lwt% SiC and Al- 3wt% SiC by mechanical milling. The microstructures of the samples were investigated by means scanning electron microscopy and correlated to their mechanical properties through hardness and three-point bending test. The experiment showed that hot press- vacuum route resulted a smaller size and amount of the pores compared to cold press- sintered, thus led to the dramatically improvement in mechanical properties which result an improvement of hardness from 105.7 Hv to 450.6 and strength from 4.7 MPa to 16.2 MPa.